Nexus between Islamic Investment, Musyarakah Financing, Islamic Microfinance and Achieving SDGs in Indonesia - WAHYUDI, HERU; LENY, SANDRA MEI (Journal of Ecohumanism, 2024)
Islamic Finance Transformation through analysing the role of musyarakah financing and Islamic microfinance in enhancing Islamic investments in Indonesia has become an important focus to achieve the Sustainable Development Goals (SDGs). This study explores the role of Islamic financial instruments in facilitating investments that not only prioritise financial returns but also social and environmental outcomes. The method used is Fully Modified Ordinary Least Squares (FMOLS) to analyse time series data from 2015 to 2023. The research variables used are Islamic investment, musyarakah financing and Islamic microfinance. The results showed that musyarakah financing has a significant influence on the growth of Islamic investment, thus contributing to poverty alleviation (SDG 1) and increasing financial inclusion (SDG 8). In addition, Islamic microfinance is proven to be effective in empowering the local economy and creating jobs. These findings confirm the importance of Islamic finance integration in sustainable development strategies and offer innovative solutions to complex global challenges